Chronopharmacological Insights: Enhancing Acetaminophen Administration Timing for Inpatient COVID-19 Management - Fendy Prasetyawan; Yuneka Saristiana; Anis Akwan Dhafin; Okky Intan Mawarni; Asrizal Azis; Ema Tri Wulan (Paspama Institute, 2024)
The global COVID-19 pandemic has posed unprecedented challenges to global health. Dr. Soedomo Regional General Hospital in Trenggalek, which is involved in the management of COVID-19 patients, has witnessed a long journey in responding to and treating individuals infected with the SARS-CoV-2 virus. The use of acetaminophen has been a primary focus in efforts to improve standards of care and understanding symptom management in COVID-19 patients. Chronopharmacological analysis of acetaminophen use in COVID-19 patients at Dr. Soedomo Hospital aims to provide insight into how the timing of drug administration can affect therapeutic responses. There is evidence that the body's circadian rhythm can influence the metabolism and pharmacological effects of drugs, but this perspective has not been fully explored in the context of COVID-19. This study involved an analytical observational approach with a Cross-Sectional design and retrospective data collection method from the medical records of COVID-19 patients treated at Dr. Soedomo Regional Hospital in Trenggalek District. The results of the study showed that acetaminophen therapy at 16.00 WIB resulted in a more significant reduction in body temperature compared to other times. A deeper understanding of the body's circadian rhythm can help optimize the benefits of therapy and reduce potential side effects. Although there are limitations to this study, these results provide a basis for the development of more targeted and personalized treatment strategies. The clinical implications of this research can help in determining the optimal timing for administering therapy to achieve desired effects in COVID-19 patients.